An analysis of epidemiological characteristics of microvascular complications and comorbidities among type 1 diabetes patients - Małgorzata Lewicka; Irmina Korzeniowska-Dyl; Dariusz Moczulski; Agnieszka Woźniak–Kosek; Magdalena Zawadzka; Gabriela Henrykowska (Acta Biochimica Polonica)
PurposeEpidemiological analysis of medical data of patients with type 1 diabetes (T1DM) and disease complications treated in hospital.MethodsA retrospective, cross-sectional study was conducted on records from 306 patients with type 1 diabetes (180 men and 126 women). The study analyzed demographic, clinical, and biological data, focusing on associations between Hashimoto’s disease, neuropathy, and retinopathy using k-means clustering.ResultsHypertension was present in 28.8%, Hashimoto’s disease in 17.6%, retinopathy in 17.6%, neuropathy in 8.2%. Multivariate logistic regression showed that the chance of retinopathy more than doubles with the coexistence of hypertension (OR 2.096, 95% Cl: 1.035–4.248) and this chance increases by 4.5% with each year of age compared to the previous year (OR 1.045, 95% Cl: 1.011–1.080). The risk of neuropathy increases by 10.8% with each year since diabetes diagnosis compared to the previous year (OR = 1.108, 95% Cl: 1.062–1.156) and the chance of this disease rises by 17.6% with each year of diabetes duration compared to the previous year (OR 1.176, 95% Cl: 1.092–1.267). Clustering was strongest in patients without comorbidities (66.3%). Only 2.3% had Hashimoto’s disease and retinopathy, 3.59% had retinopathy and neuropathy, and just 1.3% had all three conditions.ConclusionPatient age, duration of diabetes, and the presence of hypertension are key risk factors for diabetes-related complication.